2012
DOI: 10.1007/s11269-012-0114-1
|View full text |Cite
|
Sign up to set email alerts
|

Energy Production in Water Distribution Networks: A PAT Design Strategy

Abstract: Pump operating as turbine (PAT) is an effective source of reducing the equipment cost in small hydropower plants. However, the manufacturers provide poor information on the PAT performance thus representing a limit for its wider diffusion. Additional implementation difficulties arise under variable operating conditions, characteristic of water distribution networks (WDNs). WDNs allow to obtain widespread and globally significant amount of produced energy by exploiting the head drop due to the network pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
95
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 188 publications
(100 citation statements)
references
References 25 publications
0
95
0
1
Order By: Relevance
“…In WSNs, particularly in cities with considerable geodesic differences, areas exist where the pressure is greater than necessary. In certain cases, energy dissipation is imperative to minimize leakage (Carravetta et al 2012;Carravetta et al 2013;Xu et al 2014;Fecarotta et al 2015). This dissipation is usually ensured by pressure reduction valves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In WSNs, particularly in cities with considerable geodesic differences, areas exist where the pressure is greater than necessary. In certain cases, energy dissipation is imperative to minimize leakage (Carravetta et al 2012;Carravetta et al 2013;Xu et al 2014;Fecarotta et al 2015). This dissipation is usually ensured by pressure reduction valves.…”
Section: Introductionmentioning
confidence: 99%
“…Carravetta et al 2012 proposed placement in the inlet nodes of network districts. Araújo et al 2006 suggested identification of a number of nodes with energy potential within the entire network.…”
Section: Introductionmentioning
confidence: 99%
“…The use of RES includes small hydroelectric power (less than 1-3 MW) located along small rivers [1,2] or along water transmission and distribution pipeline systems [3,4] and characterized by continual changes occurring in the turbine operating conditions (discharge and/or load).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, such a plant would face a large variability of both discharge and head, due to the hourly variability of water users' demand, as well as the small amounts of available power [30,31]. Furthermore, the turbine head curve exhibits a behaviour which is completely different from the head drop curve of a regulating valve: the former increases with the discharge, while the latter decreases as the flow rate increases [32]. All these difficulties, together with the small amount of power available, hinder the use of classic turbines, due to their high price and their long payback period.…”
Section: Energy Recovery In Water Systemsmentioning
confidence: 99%